Efficacy of Subchondroplasty in the Treatment of Pain Associated With Bone Marrow Lesions in the Osteoarthritic Knee. Issue 5 (12th May 2023) - Randelli, Pietro; Compagnoni, Riccardo; Ferrua, Paolo; Ricci, Martina; La Verde, Luca; Mekky, Ahmed Farid; De Silvestri, Annalisa; Menon, Alessandra
Background: Bone marrow lesions (BMLs) are common subchondral defects revealed by magnetic resonance imaging (MRI) in patients with osteoarthritis, often associated with pain and functional limitation. Subchondroplasty (SCP) is a relatively new technique in which bone substitute material (BSM) is injected inside BML areas to provide structural support to the subchondral bone, preventing its collapse and reducing pain. Purpose/Hypothesis: The purpose of this study was to characterize changes in pain, functional and radiological outcomes, conversion to knee replacement, and complications after SCP. We hypothesized that ≥70% of patients would achieve a reduction in pain of ≥4 points on a numeric rating scale (NRS) at a 6-month follow-up after SCP. Study Design: Case series; Level of evidence, 4. Methods: Patients with symptomatic knee BMLs who underwent SCP were prospectively evaluated preoperatively and at 1, 6, 12, and 24 months postoperatively. Functional outcomes were measured with the NRS for pain, Knee Society Score (KSS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and International Knee Documentation Committee (IKDC) scores. Radiographs and MRI were performed preoperatively and at 6- and 12-month follow-ups to verify edema healing and changes in bone structure. Results: A total of 50 patients were included in the study. The mean follow-up was 26 months (24-30 months). Compared with preoperative values, the mean NRS score decreased at every follow-up point ( P < .0001 for all) and the IKDC, WOMAC, and KSS scores improved significantly at 6- and 12-month follow-ups. At 6 months postoperatively, 27 patients (54%) registered a reduction on the NRS of ≥4 points. Postoperative MRI revealed a hypointense zone surrounded by a hyperintense signal at the injection site. Standard radiography showed osteoarthritis grade worsening in 4 (8%) patients. Knee replacement was performed in 11 patients —in 7 patients due to the worsening or persistence of disabling symptoms and in 4 patients due to the progression of osteoarthritis. The leakage of BSM occurred in 6 patients without any clinical consequences during the study period. Conclusion: About half of the study patients achieved a reduction in the NRS of 4 points at the 6-month follow-up after SCP. Registration: NCT04905394 (ClinicalTrials.gov identifier).